Analyzing the Effect of Work Motivation, Work Environment, and Training on Employee Performance at SLB Negeri Pembina Palembang - Fathulrachman, Muhammad; Usman, Benny; Kurbani, Adie (Jurusan Akuntansi Politeknik Negeri Bandung, 2025)
The effectiveness of employee performance in special education institutions remains a crucial yet underexplored area within human resource management research. SLB Negeri Pembina Palembang, as a government-run school for students with special needs, has faced challenges such as declining staff morale and punctuality. This study aims to examine the effect of work motivation, work environment, and training on employee performance within this institution. Using a quantitative research approach, data were collected via a Likert-scale questionnaire from all 76 employees through saturated sampling. The data were analyzed using multiple linear regression through SPSS version 26, accompanied by classical assumption testing to ensure model validity and reliability. The findings reveal that training and the work environment have significant positive effects on employee performance, with training emerging as the most dominant factor. However, work motivation did not show a statistically significant impact in this context. Simultaneously, the three variables collectively explain 31.1% of the variance in employee performance, suggesting the presence of other influencing factors such as leadership style or organizational culture. This research contributes to the literature by highlighting the unique dynamics of human resource management in special education settings, and offers practical implications for improving employee performance through targeted training and a supportive work environment. Limitations of the study include its focus on a single institution and a limited set of variables, which may affect generalizability. Future studies are encouraged to incorporate broader organizational factors to deepen understanding in this field